2007
DOI: 10.1111/j.1600-6143.2007.01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcomes of Renal Transplantation from Cardiac Death Donors: A 30-Year Single Center Experience

Abstract: Of the 256 transplanted kidneys from DCD donors, 38 (15%) functioned immediately after transplantation. The incidence of delayed graft function (DGF) was 72%. Warm ischemic time and total ischemic time were 7.4 ± 9.4 min and 11.9 ± 5.6 h, respectively. The overall graft survival rates at 1, 5 and 10 years were 80%, 72% and 53%, respectively. Graft survival rates in each group have continually improved over time (5-year graft survival; 23% vs. 64% vs. 74% vs. 91%, respectively). However, there was no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 22 publications
3
38
0
Order By: Relevance
“…In this study, there was no difference in overall graft survival of ECD/DCD versus non-ECD/DCD. Additionally, when comparing those with DGF versus immediate graft function, there was no significant difference in the proportion of ECD kidneys with DGF (15). However, other studies have shown inferior graft survival in recipients of ECD/DCD kidneys when compared to non-ECD/DCD kidneys (16,17).…”
Section: Discussionmentioning
confidence: 82%
“…In this study, there was no difference in overall graft survival of ECD/DCD versus non-ECD/DCD. Additionally, when comparing those with DGF versus immediate graft function, there was no significant difference in the proportion of ECD kidneys with DGF (15). However, other studies have shown inferior graft survival in recipients of ECD/DCD kidneys when compared to non-ECD/DCD kidneys (16,17).…”
Section: Discussionmentioning
confidence: 82%
“…When compared with kidneys recovered from DBD, DCD kidneys have increased rates of DGF and primary non function (PNF) [15,27,30] -mainly due to increased warm ischaemia time during recovery but also due to cold ischaemia. Based on a porcine model of DCD, Jani et al [54] hypothesised that DCD kidneys have increased caspase-1 due to warm ischemia and increased caspase-3 and apoptosis due to cold ischaemia.…”
Section: Dgf and Primary Non Functionmentioning
confidence: 99%
“…Since its implementation four and a half years ago, DCD has accounted for 10.9% of deceased donor activity in Ontario, Canada [18] . The majority of DCD kidneys are from controlled donors meaning that the number of organs can be further increased by utilising uncontrolled donors [3,4,12,[19][20][21][22][23][24][25][26][27][28][29][30] although the associated workload is considerably more and the yield rate poorer. Reports from some centres show that DCD from deaths outside the hospital may be a good source of donor kidneys and may provide a way to successfully increase the donor pool for organ transplantation [31] .…”
Section: Spread Of Practicementioning
confidence: 99%
“…[7][8][9] However, this vital source of organs continues to be underutilized. [10][11][12][13][14] Over the past decade, because of severe shortage of organs, the criteria for organ donation among trauma donors have been extended to include DCD as a potential source of organ donation. However, the true utilization of DCD in trauma patients remains unknown.…”
mentioning
confidence: 99%